Influencers and influencer marketing – indispensable part of the business of modern companies - Diana Karakaš; Hrvoje Zovko (Mednarodno Inovativno Poslovanje)
With the growth of popularity and the development of social networks, appeared influencers and developed a new type of marketing, influencer marketing. Today, influencers, due to the influence they have on people, and influencer marketing, which records excellent results and helps the company achieve its business goals, are an indispensable part of the business of every modern company. The purpose of the article is to explain why influencers and influencer marketing are an important, indispensable part of the business of modern companies. Research methods which are applied in the paper are description and compilation method. By observing and researching the influence that social networks and influencers have on them authors concluded that influencer marketing will certainly continue to develop in the future and that it will gain even more importance for business operations. The paper presents the knowledge that the authors who were involved in research on influencers and influencer marketing have come to over the years. The information presented in the paper will serve other authors in researching this field.